The effect of short-term intermittent light exposure on total carbon content and quality of dark-stored ornamental chilli plants - Tengku Muda Mohamed, Mahmud; Ramlan, Mohd Fauzi; Ahmad, Siti Hajar; Kays, Stanley J. (Universiti Putra Malaysia Press, 1997)
Using ornamental chilli (Capsicum frutescens L.) as a model plant, a study was conducted on carbon balance analysis to determine the potential of using 2-3 hours of intensive light exposure per day to maintain the plant quality during 16 days storage period. Carbon input/output ratios were ascertained by measuring respiratory carbon losses and photosynthetic carbon inputs. Replacement of respiratory carbon losses (i. e. approx. 95 %) using 2-3 hours of light exposure was sufficient to maintain growth attributes (i.e. plant height, leaf area, leaf, stem, root and total dry weight).